Static and Buckling Strength Analysis for Rear Tipper Vessel TV35 with MSC Nastran 4.5 - HIMAWAN (NIM 13103011), ADHITYA
PT. United Tractors Pandu Engineering has been redesigning one of their products which is called Rear Tipper Vessel TV35. Rear Tipper Vessel itself is one of many types of truck vessel that has the ability to make a rear unloading mechanism. But because of the limitation of software ability that PT United Tractros Pandu Engineering had, this new product's strength has not been analysed yet. The new generation of Rear Tipper Vessel TV35 Scania has one big difference if being compared with the old the generation. In the new generation the stiffener that placed below the vessel has been removed. Because of that the strength analysis need to be done in static and buckling analysis. Furthermore, because of the complex shape of the vessel, all of the analysis has to be done with finite element method by using MSC Nastran 4.5 software as a modeler and also as an analysis modul. There are 3 loading condition that need to be simulated to represent the critical operational condition of that vessel. The first scenario simulate the condition at the very beginning when the vessel need to be lifted by hydraulic pump. The second scenario simulate the condition when the truck is doing braking and turning at the same time. To simulate the forces happened in that condition, the vessel's load need to be added with constants 0.8G and 0.6G for braking and turning respectively. Lastly, the third scenario is to simulate the condition when the vessel is doing a loading process with assumption the material will be fallen out from the heigth of 3 meters from the vessel's floor. The material used to simulate the load is coal material with density 0.95 ton/m3. From those analysis results can be concluded that there is a component that has a relatively high failure rate. The component is endframe 2 which is located on the back stiffener, on top of the pivot that connect the vessel to the truck chasis. According to that, PT United Tractors Pandu Engineering is suggested to change the material that made endframe 2 to a material that has a yield strength more than 300 MPa.